Thermal Performance Analysis of High-temperature Heat Transfer Process of Solar Energy - Xia, X L; Sun, F X; Tan, H P; Chen, X (KnE Materials Science, 2018)
Volumetric solar receivers (VSR) have become a promising technology for the solar thermal conversion. The absorption of the concentrated solar radiation and the heat transfer to the working fluid are the two dominant processes. Firstly, the effects of two typical modeling approaches of the concentrated solar radiation for receiver are compared in view of porosity and mean cell size. Then, the radiation transport within the solar window and the porous absorber is fully simulated. The effects of porous structure parameters, slope error of the concentrator, and the alignment error of the receiver are analyzed. Keywords: volumetric solar receivers (VSR), Monte Carlo ray tracing method, concentrated solar radiation, heat transfer